The Specification of Dynamics in Cost Function and Factor Demand Estimation - Kolstad, Charles D.; Lee, Jong-Kun (The Review of Economics and Statistics, 1993)
This paper concerns the problem of properly specifying the dynamic structure of models of industry costs and factor demands. The paper compares three common frameworks: long-run costs with all factors assumed in equilibrium (Full Static Equilibrium), short-run costs with variable factors in short-run equilibrium (Partial Static Equilibrium) followed by computation of long-run costs, and short-run costs including internal capital adjustment costs (Partial Dynamic Equilibrium). The approach of the paper is to estimate a capital-labor-fuel-electricity model for six OECD countries (G7 less Italy) for the 1960-1989 period. Using the three different 'dynamic' specifications, we obtain substantially different results in terms of factor demand, cross-price effects and technical change. The implication is that proper dynamic specification is critical. The Partial Dynamic Equilibrium model appears to behave most consistently across the cross-section. Copyright 1993 by MIT Press.